Hubungan Antara Keterampilan Membaca Cepat Dengan Kemampuan Pemahaman Isi Bacaan Siswa Kelas V Sekolah Dasar - dona, ayu prima; Mahjuddin, Ritawati; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims to determine the relationship between fast reading skill with the ability to understanding the content of reading class students SDN Gugus II subdistrict Koto tangah Padang city. Type  of research is correlation with number of sample 52 student, implemented in class V SDN 17  Bungo Pasang  and SDN 45 Bungo Pasang. Test results prove between fast reading skill and understanding the contents of reading strong correlated. Correlation coefficient value of 0,721 and t count value 7.335 > t table 2.02 with a significance level of  0.05%, coefficient of determination 52%.  It can be concluded that fast reading skill has significant correlation with the ability to understanding the content of reading 52%.Keywords: fast Reading Skills, Understanding the Content of Reading